KONSEP PENGENALAN ALLAH (MA’RIFATULLAH) IMPLIKASINYA TERHADAP PENDIDIKAN AGAMA ISLAM - Hasbiyallah Hasbiyallah; Mahli Nurul Ihsan (Jurnal Perspektif, 2019)
The purpose of this writing is to analyze the concept of introduction to Allah (Ma’rifatullah) in Islamic education and explain the Implications of Ma'rofatullah in Islamic religious education. This research method uses a qualitative approach to the library method (search library) through explanations of interpretations to explain the concept of Ma’rifatullah in the Qur'an and then implies Islamic education. As for the results of the research, first, the concept of introduction to Allah (Ma’rifatullah) can be learned through reflection and deepening of thoughts on verses Qauniah (revelation) and verses of Aqliyah (universe) so that the introduction can thrill mind awareness and faith in God and cause love worship to Him. Second. The implications of Ma’rifatullah in Islamic education include: a) Ma’rifatullah as a basic education of Islam to increase morale and students, b) Recognizing the Duties and Responsibilities of Students as Abdullah, c) Ma’rifatullah As awareness of the duties and roles of students as Caliph on earth, d) Reach Ridho Allah as the Main Purpose of Islamic education and e) Ma’rifatullah as Noble Moral Education for Students.